Organocatalyzed Aldol Reaction between Pyridine‐2‐carbaldehydes and α‐Ketoacids: A Straightforward Route towards Indolizidines and Isotetronic Acids. Issue 43 (13th September 2013) - Liautard, Virginie; Jardel, Damien; Davies, Clotilde; Berlande, Muriel; Buffeteau, Thierry; Cavagnat, Dominique; Robert, Frédéric; Vincent, Jean‐Marc; Landais, Yannick
Abstract Enantioselective aldol reactions between substituted pyridine carbaldehydes and α‐ketoacids were shown to provide isotetronic acids or their corresponding pyridinium salts, depending on the nature of the substituents on the pyridine ring. The pyridinium salts were generated through nucleophilic attack of the pyridine nitrogen atom onto the reactive keto functional group. Moderate‐to‐good yields of both compounds were typically obtained and high levels of enantioselectivity were observed by using benzimidazole pyrrolidine I as a catalyst. Hydrogenation of the resulting pyridinium salts led to new indolizidines with high ee values and diastereocontrol. X‐ray diffraction studies allowed the determination of the relative configuration of the products. Finally, DFT calculations were performed to rationalize the divergent pathway as a function of the pyridine substituents.